An update on the biological characteristics and functions of tuft cells in the gut - Du, Yixuan; Gao, Han; He, Chengwei; Xin, Shuzi; Wang, Boya; Zhang, Sitian; Gong, Fengrong; Yu, Xinyi; Pan, Luming; Sun, Fanglin; Wang, Wen; Xu, Jingdong (Frontiers in Cell and Developmental Biology, 2023)
The intestine is a powerful digestive system and as well as one of the most sophisticated immunological organs. Evidence shows that tuft cells (TCs), a kind of epithelial cell with distinct morphological characteristics, play a significant role in a variety of physiological processes.TCs can be broadly categorized into different subtypes depending on their specific molecular criteria. In this review, we discuss its biological properties and impact on maintaining gastrointestinal homeostasis. We also emphasize its relevance to the immune system and highlight its powerful influence on intestinal diseases. In addition to the impact of TCs on intestinal inflammation and neoplasia, we provide fresh insights into future clinical diagnostic and therapeutic strategies related to TCs.